Geometric mean ratio-dependent scaled bioequivalence limits with leveling-off properties - Karalis, V.; Macheras, P.; Symillides, M (EUROPEAN JOURNAL OF PHARMACEUTICAL SCIENCES, 2005)
In this study, novel approaches for the design of bioequivalence (BE) limits are developed. The new BE limits scale with intrasubject variability but only until a geometric mean ratio (GMR)-dependent plateau value and combine the classic (0.80-1.25) and expanded (0.70-1.43) BE limits into a single criterion. Plots of the extreme GMR values accepted as a function of coefficient of variation (CV) have a convex shape, similar to the classic unscaled 0.80-1.25 limits. The performance of the novel approaches in comparison to the classic unscaled 0.80-1.25 limits as well as the two expanded BE limits, i.e., 0.70-1.43 and 0.75-1.33 was assessed using simulated data. Two-period crossover BE investigations with 12, 24 or 36 subjects were simulated with assumptions of CV 10%, 20%, 30% or 40%. At low CV values, the performance of the novel BE limits is almost identical to the 0.80-1.25 criterion. On the contrary, the expanded BE limits are very permissive even at high GMR values. For high CV% values (30% and 40%), the new BE limits show a much greater probability of declaring BE when GMR = 1 in comparison to the classic 0.80-1.25 limits. In addition, when the drug products differ more than 25%, the new BE limits show much lower percentage of acceptance than the expanded 0.70-1.43 limits. One of the major advantages of the new BE limits is their gradual expansion with variability until a GMR-dependent plateau value. Finally, the continuity and leveling-off properties of the new BE limits make them suitable for the assessment of BE studies, irrespective of the level of variability encountered. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: bioequivalence; GMR; highly variable drugs; regulatory criteria; scaled bioequivalence limits